Esophageal submucosal gland duct adenoma: a case report and literature review - Zhou, Bing; Zheng, Jian; Huang, Ling; Hao, Hua (Frontiers in Oncology, 2025)
IntroductionEsophageal submucosal gland duct adenoma (ESGDA) is a rare, benign tumor with non-specific clinical features and imaging findings, often leading to misdiagnosis.Case reportIn this report we describe the clinicopathological features of a new-onset case of ESGDA and review 19 previously-reported ESGDA cases in the literature.ResultsThe median age of the 20 patients was 70 years, and the male-to-female ratio was 5:2. Lesions located in the lower esophagus accounted for 81% of the cases. Chest and abdominal discomfort were the main clinical symptoms, and endoscopic findings mostly included polypoid masses that were impossible to correctly diagnose prior to excision and biopsy. On microscopic examination, the submucosal tumor was found to be composed of glandular cavities of various sizes, bland cytology with infrequent mitotic figures, and the interstitium was infiltrated by a large number of lymphocytes. Immunohistochemical analysis revealed the expression of adenomyoepithelial cytokeratins (CK) CK7, CK5/6, and p63. Local tumor resection was performed, the longest follow-up period was 132 months of the 20 patients, the prognosis was favorable, and no recurrence or metastasis.DiscussionESGDA is more common in the lower esophagus in elderly patients, and its clinical symptoms are atypical. Taking into account its characteristic microscopic morphology and immunohistochemical markers, the possibility of this rare disease should be considered to avoid misdiagnosis or missed diagnosis. Complete en bloc resection with Endoscopicp may be the best strategy for both the diagnosis and treatment of this entity.